Hubungan Brand Activation The Interns Generation G dengan Citra PT Gudang Garam Tbk - zelvina zora; Tresna Wiwitan (UNISBA Press, 2022)
Abstract. A brand that had been active in the market, well known and able to provide the quality and satisfaction appointed through advertising or other. hotchpotch of marketing communications. Through activation, brand able to see consumer brand as a single piece intact everywhere consumers find it both in traditional and digital media. Activation brand to be a medium of communication on the promotion of good message has been especially through integrated marketing communications. Hotchpotch A company set of strategies for marketers propelled sales promotion through tools so that it can build a brand. Research purposes to know the brand activation through marketing activation, social media activation, promotions activation, marketing activation event, sponsorship activation with PT. Gudang Garam Tbk?. The method used in this study is the correlational method. That is the method for researching and knowing the relationship between two variables (X and Y). In the calculation, the correlation coefficient will be obtained, this correlation coefficient is used to determine whether there is a strong relationship, the direction of the relationship, which means whether or not there is a relationship. In this research, respondents were researchers is 100 respondents from followers instagram generation _. g.id. in using random sample. Drawing conclusions, there are powerful relationship between direct marketing, social media, promotion activation, marketing event, sponsorship activation with image PT. Gudang Garam Abstrak. Sebuah brand yang sudah aktif dikenal baik di pasar, dan mampu memberikan kualitas dan kepuasan yang sudah dijanjikan melalui iklan atau bauran komunikasi pemasaran lainnya. Melalui brand activation, konsumen mampu melihat brand sebagai satu bagian utuh di mana pun konsumen menemukannya baik di media digital maupun tradisional. brand activation mampu menjadi media komunikasi yang dapat dengan baik meneruskan pesan promosi yang telah dilakukan terutama melalui bauran komunikasi pemasaran yang terpadu. Pemasar sebuah perusahaan mengatur strategi untuk mendorong penjualan melalui alat-alat promosi sehingga dapat membangun sebuah brand. Tujuan penelitian untuk menetahui hubungan brand activation melalui marketing activation, social media activation, promotions activation, mamarketing eventactivation, sponsorship activation dengan PT. Gudang Garam Tbk. Metode yang digunakan dalam penelitian ini adalah metode korelasional. Yaitu metode untuk meneliti dan mengetahui hubungan antara dua variabel (X dan Y). Di dalam perhitungannya nanti akan didapatkan koefisien korelasi, koefisien korelasi ini digunakan untuk mengetahui apakah ada hubungan yang kuat, arah hubungan, yang berarti ada atau tidak ada hubungan tersebut. Dalam penelitian ini, responden yang dipilih peneliti adalah 100 responden dari followers instagram generation_g.id.dengan menggunakan random sampel. Simpulan, terdapat hubungan yang kuat antara direct marketing, social media, promotion activation, marketing event, sponsorship activation dengan citra PT Gudang Garam.